An efficient approximate analytical technique for the fractional model describing the solid tumor invasion - Chethan, H. B.; Saadeh, Rania; Prakasha, D. G.; Qazza, Ahmad; Malagi, Naveen S.; Nagaraja, M.; Sarwe, Deepak Umrao (Frontiers in Physics, 2024)
In this manuscript, we derive and examine the analytical solution for the solid tumour invasion model of fractional order. The main aim of this work is to formulate a Solid tumour invasion model with the aid of the Caputo fractional operator. Here, the model involves a system of four equations which are solved using an approximate analytical method. We used the fixedpoint theorem to describe the uniqueness and existence of the model's system of solutions, and graphs to explain the results we achieved using this approach. The technique used in this manuscript is more efficient for studying the behaviour of this model, and the results are accurate which converge swiftly. The current study reveals that the investigated model is time dependent, which can be explored using the fractional order calculus concept.